2023
DOI: 10.3390/molecules28041658
|View full text |Cite
|
Sign up to set email alerts
|

Discovery of Anti-Inflammatory Triterpenoid Glucosides from the Heritiera littoralis Dryand

Abstract: Two new triterpenoid glucosides, Heritiera A (1) and Heritiera B (2), and six known triterpenoid analogs (3–8) were isolated from Heritiera littoralis Dryand. Their structures were identified by comprehensive spectroscopic analyses and comparisons with the literature. The anti-inflammatory activity of the isolates from H. littoralis was evaluated using a lipopolysaccharide (LPS) stimulated RAW 264.7 cells model. The result showed that four triterpenoids exhibited potent anti-inflammatory activity. Among these … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 32 publications
1
0
0
Order By: Relevance
“…Prior research has indicated that the diversity of the H. littoralis community decreases from the coast of adjacent seas to the marsh of inland seas [43]. Based on the distribution map of H. littoralis we have generated, the suitability index is higher closer to the sea area, which is consistent with the general suitability of mangrove plants.…”
Section: Ecologically Suitable Areas In Chinasupporting
confidence: 76%
“…Prior research has indicated that the diversity of the H. littoralis community decreases from the coast of adjacent seas to the marsh of inland seas [43]. Based on the distribution map of H. littoralis we have generated, the suitability index is higher closer to the sea area, which is consistent with the general suitability of mangrove plants.…”
Section: Ecologically Suitable Areas In Chinasupporting
confidence: 76%